Contribuição da criação de uma unidade de conservação no sequestro de carbono atmosférico. - Zampar, Rafael (2009)
The atmospheric concentration of CO2, the main cause of global warming, has been the highest since the human species origin. Thus, this study was conducted to evaluate the contribution of the creation of the Environmental Protection Area of Ilhas e Várzeas do Rio Paraná (EPA-IVRP) to the atmospheric carbon fixation. The secondary forests developed in the last 10 years in five islands from the region of upper Paraná River floodplain were mapped; the carbon from above and belowground plant biomass was quantified using allometric equations; and the potential generation of certified emission reductions (CERs) was calculated. The area of islands covered with forests has doubled in 10 years of the creation of the EPA-IVRP, resulting in the fixation of 60,1 Mg C ha-1, at the rate of 6,01 Mg C ha-1year-1. If there was a project of clean development mechanism established in the area, it could have been generated around 110.000 CERs. This study showed that the creation of the EPA-IVRP contributed to the forest recovering and the atmospheric carbon sequestration. The methodology proposed in this work can be adopted in posterior studies to monitor the carbon stocks in the phytoecological regions of the Semi-Deciduous Seasonal Forest, in the same climatic zone. Therefore, it is important to monitor periodically the carbon stocks in the conservation units.